The Influence of Mathematics Anxiety on Mathematical Abstraction Abilities with Self-Concept as a Mediator Variable - Destiana, Lusi Riska; Septianawati, Erni; Syamsudin, Ahmad (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
This study aims to determine whether mathematics anxiety affects mathematical abstract ability, with self-concept acting as a mediator variable. The research type is survey research with a quantitative approach. The study was conducted at SMA Negeri Kandat. The population of this research consists of all 12th-grade students at SMA Negeri Kandat. The sampling technique used was simple random sampling, with a sample size of 100 students from the 12th grade of SMA Negeri Kandat. Data collection techniques included test methods involving the administration of mathematical abstraction ability tests and non-test methods using a mathematics anxiety scale. Data analysis was conducted using descriptive and inferential statistical analysis, which comprised prerequisite tests and hypothesis testing. The data collection procedure began with administering the mathematics anxiety and self-concept scales to the research sample. The next stage involved conducting mathematical abstraction ability tests on the research sample. The results of the study indicate that (1) mathematics anxiety among 12th-grade students at SMA Negeri Kandat affects students’ mathematical abstraction ability by 30.6%, (2) there is an influence of mathematics anxiety on students’ self-concept by 25.5%, (3) there is no influence of self-concept on student’s mathematical abstraction ability by 37%, and (4) self-concept can serve as a mediator variable between mathematics anxiety and student’s mathematical abstraction ability. These findings were obtained based on questionnaires and mathematical abstraction ability tests conducted with the students.